Analisis Pemikiran Linguistik Pedagogis Dr. V. Abdurrahim dalam Penyusunan Kitab Durus al-Lughah al-’Arabiyyah dan Implikasinya terhadap Pembelajaran Bahasa Arab / An Analysis of Dr. V. Abdurrahim’s Pedagogical Linguistic Thought in the Compilation of the Durus al-Lughah al-’Arabiyyah Textbook and Its Implications for Arabic Language Learning - Andi Nanda Anisa; Haniah Haniah; Amrah Kasim; Hamzah Hamzah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
This study aims to analyze the pedagogical linguistic thought of Dr. V. Abdurrahim underlying the compilation of Durus al-Lughah al-’Arabiyyah and to examine its implications for teaching Arabic to non-native speakers. Employing a qualitative approach with content analysis, this research investigates the structure of instructional materials, the presentation of linguistic rules, and the types of exercises found in Durus al-Lughah al-’Arabiyyah. The findings reveal that Dr. V. Abdurrahim’s linguistic thought reflects applied linguistic principles characterized by a communicative orientation, a gradual progression from simple to complex structures, and an integration of grammatical competence with language skills. These results indicate that Durus al-Lughah al-’Arabiyyah functions not merely as a practical textbook but also as a pedagogically grounded representation of applied linguistics in Arabic language teaching. This study contributes to the scholarly discourse on linguistic thought in Arabic pedagogy and offers conceptual insights for the development of communicative and contextual Arabic teaching materials.Penelitian ini bertujuan untuk menganalisis pemikiran linguistic pedagogis Dr. V. Abdurrahim yang melandasi penyusunan kitab Durus al-Lughah al-’Arabiyyah serta mengkaji implikasinya terhadap pembelajaran bahasa Arab bagi penutur non-native. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi (content analysis) terhadap struktur materi, penyajian kaidah bahasa, dan bentuk latihan dalam kitab Durus al-Lughah al-’Arabiyyah. Hasil penelitian menunjukkan bahwa pemikiran linguistik Dr. V. Abdurrahim mencerminkan prinsip linguistik terapan yang menekankan pendekatan komunikatif, gradasi struktural dari bentuk sederhana ke kompleks, serta integrasi antara penguasaan struktur bahasa dan keterampilan berbahasa. Temuan ini menunjukkan bahwa Durus al-Lughah al-’Arabiyyah tidak hanya berfungsi sebagai bahan ajar praktis, tetapi juga merepresentasikan kerangka linguistik pedagogis yang relevan dengan kebutuhan pembelajaran bahasa Arab modern. Penelitian ini berkontribusi dalam memperkaya kajian pemikiran tokoh dalam pengajaran bahasa Arab serta memberikan landasan konseptual bagi pengembangan bahan ajar bahasa Arab yang lebih komunikatif dan kontekstual.